The association between MNA and PG-SGA malnutrition assessment and the quality of life among hemodialysis patients - Achmad Rifai; Dwi Soelistyoningsih; Jonny Karunia Fajar; Atma Gunawan (Elsevier, 2022)
Background: The simple nutritional assessment tools by Mini Nutritional Assessment (MNA) and Patient Generated Subjective Global Assessment (PG - SGA) was proposed to affect the Quality of Life (QOL) in hemodialysis patients. However, currently, no evidence assessed the potency of MNA and PG - SGA for predicting the QOL in hemodialysis patients. Objective: To assess the potential implication of MNA and PG-SGA nutritional tools and the QOL among hemodialysis patients. Methods: A cross - sectional study was performed in Universitas Muhammadiyah Malang Hospital, Malang, Indonesia. A validated Kidney Disease Quality of Life - 36™ (KDQOL - 36™) instrument was used to assess the QOL. The nutritional status was assessed using MNA and PG - SGA checklist. The association between nutritional status and QOL was determined by using multiple logistic regression. Results: A total of 96 hemodialysis patients was enrolled in our study. Of them, good QOL was observed in 75 patients (78.12%). We found that hemodialysis patients with higher MNA score and lower PG - SGA score was associated with good QOL. We also found that normal MNA nutritional status was associated with good QOL. Moreover, we also found that the score of MNA ≥23.75 and PG - SGA score ≤3,5 were associated with good QOL. Conclusion: MNA and PG-SGA nutritional assessment tools are the important indicator in predicting the QOL in hemodialysis patients.